GRIEF PASTORAL DALAM PANDANGAN MAJELIS JEMAAT GMIST MUSAFIR KOTA MANADO - Yohan Brek; Toar Umbas (POIMEN Jurnal Pastoral Konseling, 2020)
ABSTRACT Pastoral Grief referred to in this study is a pastoral service to those who are grieving especially to the congregation of GMIST in the City of Manado. The pastoral duty must be carried out by Church councils in this case the Pastor, Elder and Deacon. Based on observations and interviews with Church councils, it was found that the pastoral care of grief for them only applies when a person dies and that is only a consolation and funeral service. Even though talking about grief does not only apply to people whose closest relatives die. This prompted researchers to conduct further research on Church councils in the GMIST congregation of Musafir Manado City. This study aims to find out how the understanding and practice of special servants about the task of the Pastoral Grief service and what the impact of the service results and the meaning obtained for the development of the Grief Pastoral service for Church councils in the congregation of GMIST Musafir in Manado. This study uses a qualitative approach with descriptive research methods which will describe in full the purpose of the study so that it is expected to get valid and scientific results about the understanding of special servants regarding Pastoral Grief.